Unilateral hearing loss: case report on the insidious consequence of nasopharyngeal tuberculosis - Zainal Abidin, Muhammad Hosni; Abdul Wahab, Azwan Halim (Springer, 2023)
Background: Nasopharyngeal tuberculosis constitutes 1% of the head and neck manifestation of extra-pulmonary tuberculosis. The rarity of the disease along with its non-specific presentation may pose a challenge in diagnosis. Case presentation: We present a case of a 33-year-old patient who presented with a gradual onset of unilateral hearing loss. Endoscopic examination revealed leukoplakic lesions over the bilateral torus tubarius with audiological assessment revealing a mixed hearing loss in the left ear. Patient completed a 6-month course of anti-tuberculous therapy with a complete resolution of nasopharyngeal lesions and hearing loss. Conclusion: We hypothesize that tuberculosis of the nasopharynx may not only lead to impaired middle ear ventilation but also damage to the ossicular chain and inner ear structures.